Płeć jako filtr interpretacyjny w badaniach nad relacjami rodzinnymi. Trzy przykłady konstruowania metodologicznych założeń projektów = Gender as an interpretative filter in research on family relationships: three examples of constructing methodological assumptions for projects - Ostrouch-Kamińska, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to show the possibilities and analytical potential of using a gender filter in the analysis of certain fragments of social reality, in this case everyday life and the marital and family relationships, as well as the methods of studying the gender category itself. To achieve the desired result, three research projects were presented. All of them were located within imperative paradigm, in which family relationships of women (biographical research), men (i.e., focused group interviews) and both spouses together (family phenomenology) were subsequently analyzed.
Keywords: płeć; badania nad rodziną; interpretywizm; gender; research on family; interpretivism